THE APPLICATION OF GENRE BASED APPROACH IN THE TEACHING OF ENGLISH TO THE EIGHTH GRADERS - Cicin Only Tachia; Bambang A Loeneto (Faculty of Teacher Training and Education, Universitas Sriwijaya, 2018)
Abstract: The aims of this study aimed to find out whether or not Genre Based Approach was effective to be used in teaching English for eighth graders of SMP Negeri 1 Indralaya Utara. The key informants of this study were the teachers of English, the English subject supervisor, and the students of grade eight. The method of this study was qualitative descriptive research. The qualitative data were obtained through interview, observation, and documentation. The result showed that the genre based approach was not effectiveuse for the students of eighth graders of SMP Negeri 1 Indralaya Utara, even though the teacher had applied all of the steps in genre based approach. The results of this study showed that not more than half students succeed in achieving the passing grade of English subject and the rest still got score under the passing grade. Keywords: effectiveness, genre based approach, teaching English